Teaching Grammar in the Lower-Secondary Education - Skalická, Adéla (Univerzita Pardubice, 2023)
The thesis aims to determine whether teachers use a deductive or inductive approach to teach grammar in lower-secondary education and why. First, it describes communicative competence as achieving it is the main goal of English language teaching. Then it follows up with a description of grammar and focuses on the development of grammar teaching, which reflects the development of communicative competence. Consequently, the deductive and inductive approaches are closely described with their advantages and disadvantages. The last chapter of the theoretical part concerns the lower-secondary learner and the teacher, as they are both important in learning and teaching. The practical part includes analyses of nine observed lessons and interviews with three teachers, determining the more used approach.
Výuka gramatiky na druhém stupni ZŠ
Keywords: komunikační kompetence; induktivní přístup; deduktivní přístup; gramatika; vyučování gramatiky; communicative competence; inductive approach; deductive approach; grammar; grammar teaching